TiO2 Hollow Spheres With Flower-Like SnO2 Shell as Anodes for Lithium-Ion Batteries - Weng, Ying; Zhang, Ziying; Zhang, Huizhen; Zhou, Yangyang; Zhao, Xiaona; Xu, Xingran (Frontiers in Chemistry, 2021)
SnO2 is a promising anode material for lithium-ion batteries due to its high theoretical specific capacity and low operation voltage. However, its poor cycling performance hinders its commercial application. In order to improve the cycling stability of SnO2 electrodes, novel flower-like SnO2/TiO2 hollow spheres were prepared by facile hydrothermal method using carbon spheres as templates. Their flower-like shell and mesoporous structure highlighted a large specific surface area and excellent ion migration performance. Their TiO2 hollow sphere matrix and 2D SnO2 nano-flakes ensured good cycle stability. The electrochemical measurements indicated that novel flower-like SnO2/TiO2 hollow spheres delivered a high specific capacity, low irreversible capacity loss and superior rate performance. After 1000 cycles at current densities of 200 mA g-1, the capacity of the flower-like SnO2/TiO2 hollow spheres was still maintained at 720 mAh g-1. Their rate capacity reached 486 mAh g-1 when the current densities gradually increase to 2000 mA g-1.